KEJAHATAN DALAM PERDAGANGAN INTERNASIONAL: PERLINDUNGAN HUKUM PRODUK PERTANIAN LOKAL DALAM PASAR BEBAS - Ika Riswanti Putranti; Satwika Paramasatya (Jurnal Ekonomi Dan Bisnis, 2015)
Free  trade  zone  established  under  international  treaty  instrument  provides  the  facility  specifically applies  only to member States. Main facilities  provided under such agreement covering reduction or even  elimination  of  tariff barriers  aimed  to  increase  trade  between  members,  yet  it  is  vulnerable  to trade  crimes  committed  by  third  parties  in  order  to  take  benefits.  Origin  fraud  known  as  one  of international trade crime that causes an injury for beneficiary countries. Regulatory instruments under international, regional, national, and regional dimensions, which aimed to prevent or to minimize the trade crimes become indispensable tools to avoid the losses of local producers.